A Case of Oligospermic Male Infertility Successfully Treated with Personalised Homoeopathic Medicine Phosphoricum acidum - Dey, Joy Kumar; Dey, Sanjay Kumar; Pramanik, Abhishek (Homœopathic Links, 2023)
A 25-year-old Indian, male being married for two years presented with complaints of low sperm count for one year at Homoeopathic Seva Niketan, Durga Park, New Delhi, India. The patient came to the clinic with complaints of oligospermia or oligozoospermia, headache, weak memory, and constipation. The couple had undergone various medical tests and sought the help from various infertility specialists and were told that the wife had no medical condition preventing them from having a child. The patient was treated on the wholistic concept of homoeopathy with specific doses of Phosphoricum acidum resulting in fruitful conception within three years. These were evident from the time to time semen analysis reports of the patient and presence of a live foetus in his wife's diagnostic reports.
Keywords: oligospermia; sperm count; homoeopathy; Phosphoricum acidum; conception; male infertility